Mapping Indonesia's Covid-19 Death Case with Comorbidities Using Correspondence Analysis - Melinda Putri Utami; Rosita Kusumawati (Jurnal Matematika Sains dan Teknologi, 2023)
This research aims to map and identify COVID-19 deaths with comorbidities in Indonesia using correspondence analysis. The data collection technique involved the analysis of 6231 samples of COVID-19 death cases with comorbidities in Indonesia from the official website of the COVID‑19 Response Acceleration Task Force. The variables used were the number of COVID-19 deaths with comorbid hypertension, diabetes mellitus, cardiovascular disease, chronic obstructive pulmonary disease, kidney disease, immune disorders, liver disease, cancer, asthma, pregnancy, tuberculosis, and other respiratory disorders. The findings from this study divide four groups of provinces with characteristics: Group One with the characteristics of COVID-19 death cases with comorbid hypertension, diabetes mellitus, heart disease, kidney disease, lung disease, immune disorders, and cancer; Group Two with the characteristics of COVID-19 death cases with comorbid pregnancy, liver disease, and tuberculosis; Group Three with the characteristics of COVID-19 death cases with comorbid asthma; and Group Four with the characteristics of COVID-19 death cases with other comorbid respiratory disorders.